Tren Penelitian Kepesantrenan (Studi Bibliometrik terhadap Skripsi Bertema Pesantren di Fakultas Tarbiyah IAI Al-Qolam Malang Tahun 2015-2022): (Studi Bibliometrik terhadap Skripsi Bertema Pesantren di Fakultas Tarbiyah IAI Al-Qolam Malang Tahun 2015-2022) - Muhammad Hilal (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
In the midst of the thriving research on pesantren, almost none of the research has been studied using a bibliometric approach. This was in contrast to bibliometric studies toward researches in other fields. To fill this gap, this research was carried out with a specific purpose to determine the trend of research on the theme of pesantren in theses produced by students of the Faculty of Tarbiyah IAI Al-Qolam Malang for seven years, from 2015 to 2022. Bibliometric method was conducted here to trace the rate of productivitiy, the map of themes, the map of supervision, and the types of research in those theses. The result of this research showed that there are 197 pesantren-themed theses produced by the students of the Faculty of Tarbiyah IAI Al-Qolam Malang in the above mentioned periode. From that amount, there were five themes, that is ‘kiai’ (8,63%), ‘mosque’ (8,12%), ‘santri’ (27,92%), ‘pondok’ (30,96%), and ‘teaching religious sciences’ (24,37%). All those themes were spread to 40 supervisors. The most frequent type of research used by the studests to study pesantren was qualitative one (89,34%), followed by quatitative type of research (8,12%), then Class Action Research (1,52%), and finally mixed method and Research & Development (each 0,51%). Keywords: research trend, pesantren studies, bibliometric